Classical economics and modern theory: Studies in long-period analysis - Heinz D. Kurz; Neri Salvadori (Routledge, 2003)
In this thought-provoking book, well known economists Kurz and Salvadori cover original findings and new vistas on old problems. They cover: alternative interpretations of classical economists new growth theory the relationship between Sraffian theory and Von Neumann the treatment of capital in neoclassical long-period theory. Incorporating cutting-edge research and new work, this book will be of great interest to those working in the field of the history of economic thought.
Keywords: 330; Klassische Ökonomie; Wirtschaftstheorie; Endogenes Wachstumsmodell; Produktionstheorie; Erschöpfbare Ressourcen; Theorie